Effects of mFOLFOX6 regimen combined with carrelizumab on immune function and prognosis in patients with microsatellite instability colorectal cancer - Sun, Jie; Yao, Ninghua; Lu, Pengpeng; Wang, Yan (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effect of the mFOLFOX6 regimen combined with SHR-1210 on immune function and prognosis in patients with microsatellite instability CRC. For this purpose, 60 patients with microsatellite instability CRC in our hospital from January 2019 to October 2020 were randomly divided into control and observation groups. The control group was treated with the mFOLFOX6 regimen, and the observation group was treated with s SHR-1210. After continuous treatment for 3 months, the clinical effects of the two groups were compared; CD4+, CD8+, CD4+/CD8+; IgA, IgG, IgM; Incidence of adverse reactions and PFS. The results showed that compared with the control group (30.00%), the total clinical effective rate in the observation group (53.33%) was significantly higher (P < 0.05). After treatment, CD4+, CD4+/ CD8+ decreased significantly and CD8+ increased significantly, and the change range of the observation group was significantly less than the control group (P < 0.05. The levels of IgA, IgG and IgM in the two groups decreased significantly after treatment, and the decrease in the observation group was significantly less than the control group (P < 0.05). There was no significant difference in the incidence of abnormal liver function, bleeding, proteinuria, neurotoxicity, gastrointestinal reaction, leucopenia and hypertension between the two groups (P > 0.05). PFS in the observation group was significantly prolonged after treatment (P < 0.05). In general, the mFOLFOX6 regimen combined with SHR-1210 is effective in the treatment of microsatellite instability CRC. It can not only improve the immune function, but also not increase adverse reactions, prolong the survival time, and has a high clinical reference value.